Pricing decision in a multi-period hub location problem under uncertainty: a mathematical model. (25th November 2021) - Bidoki, Mahdieh Zare; Galankashi, Masoud Rahiminezhad; Setak, Mostafa
This research develops a multi-period mathematical model to address the hub covering location problem (HCLP) considering competitiveness, pricing, demand uncertainty and congestion. Although the HCLP is investigated in previous studies, concurrent investigation of these issues is less investigated. To fill the gap, this study models the HCLP with regard to aforementioned issues to maritime transportation problem. Particularly, it is assumed that the products are perishable and should be delivered in a specific time, the hubs' capacities are limited, and they face congestion if the demand exceeds a defined value. An M/M/C queue system is applied to deal with the congestion. A nonlinear mathematical model is proposed and a medium-sized case study is applied to address the concerns of this research. According to the results, customers are highly interested in competitive criteria of price and delivery time. Based on sensitivity analysis, price significantly affects the competitiveness and capability of absorbing new customers.